If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35x + 42 = 0 Reorder the terms: 42 + -35x = 0 Solving 42 + -35x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -35x = 0 + -42 Combine like terms: 42 + -42 = 0 0 + -35x = 0 + -42 -35x = 0 + -42 Combine like terms: 0 + -42 = -42 -35x = -42 Divide each side by '-35'. x = 1.2 Simplifying x = 1.2
| f(x)=3x^2-18x+1 | | .666x=180 | | 5/8x=17 | | x^3-x^2-75/8=0 | | 5/8t=-10 | | y-4=5(x+3) | | 2(x+4)=-36 | | 3y=2y+24 | | 8x^3+8x^2-75=0 | | 3*5+5y=45 | | -(9n-2)-15-c-n= | | X^2+12=25 | | 3.5x+5= | | 7w+1=-4w | | 7(7x+1)=49x+7t | | 3x+5*0=45 | | Y=2x-66 | | 4+x=30 | | y=-8-11 | | 10t+4=8t+6 | | 43b=6b-5 | | 12=3+5x-2x | | 3*0+5y=45 | | 2+(3x+8)+(x+2)=16 | | -2+p/1=0 | | -4y+-y=-3 | | -4x-104/12 | | (4x)+(x+4)+(x)=76 | | 10g^3-3g= | | -2log(x+8)=4-2log(x-7) | | (-3x^3y^-2)^3/(9x^-4y^-3)^2 | | 15-3x= |